Adapting the number of validator according the need in a BFT chain with SABINE. Issue 8 (2022) - Leduc, Guilain; Kubler, Sylvain; Georges, Jean-Philippe
Abstract: Blockchain is a revolutionary technology asserting the integrity and the share of data between untrusted users and without central authority.In case of private and non-publicly accessible networks, more energy efficient consensus can be adapted than permissionless consensus such as consensus used in cryptocurrency. Theses permissionless consensuses are called BFT consensus and are based on communication between participants of the network. By design, latency and throughput of transaction commitment are impacted by the number of participants because an agreement with more participants takes more time. On the contrary, a chain shared with more participants is more secure to a same number of malicious users. Theses two properties implies that the number of validator is a trade off between security and performances that can potentially evolve according to demands. The present research proposes Sabine (Self-Adaptive BlockchaIn coNsEnsus protocol) a new consensus based on PBFT to optimally and dynamically adapt the pool of validator in order that the output transaction throughput meets the input transaction throughput, with a minimum limit on the number of validators, implying a more reactive chain, with less latency. An evaluation of Sabine on the Grid5000 shows a relative error between this throughput of 4.45% compared to 67.6% for a classic chain.